2022
DOI: 10.21037/tau-22-355
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sarcopenia in bladder preservation therapy for muscle-invasive bladder cancer patients: a narrative review

Abstract: Background and Objectives: Muscle-invasive bladder cancer (MIBC) is a biologically aggressive disease and its prognosis is poor. Radical cystectomy (RC) with urinary diversion and lymph node dissection is the gold standard treatment for MIBC patients. Accumulating evidence indicates that sarcopenia, the degenerative and systemic loss of skeletal muscle mass, is a significant predictor of higher rates of mortality and perioperative complications following RC. Recently, bladder preservation therapy has been offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Bladder cancer patients may experience malnutrition due to the impact of the tumor on the body's metabolism and absorption, or due to adverse reactions during treatment, such as loss of appetite, nausea, and vomiting. Besides, bladder cancer patients with sarcopenia may have reduced tolerance to surgical and chemotherapeutic treatments, and the disruption of the body's immune and metabolic functions may interfere with the normal response to these treatments [33]. In the past years, the association between sarcopenia and prognosis in cancers has been widely reported and revealed.…”
Section: Plos Onementioning
confidence: 99%
“…Bladder cancer patients may experience malnutrition due to the impact of the tumor on the body's metabolism and absorption, or due to adverse reactions during treatment, such as loss of appetite, nausea, and vomiting. Besides, bladder cancer patients with sarcopenia may have reduced tolerance to surgical and chemotherapeutic treatments, and the disruption of the body's immune and metabolic functions may interfere with the normal response to these treatments [33]. In the past years, the association between sarcopenia and prognosis in cancers has been widely reported and revealed.…”
Section: Plos Onementioning
confidence: 99%
“…In murine models, the administration of FOLFIRI (5-FU, leucovorin, irinotecan) and FOLFOX (5-FU, leucovorin, oxaliplatin) leads to weight loss, adipose tissue loss, skeletal muscle wasting, weakness, and involves mechanisms such as the hyperactivation of catabolic signaling pathways, sarcomere structural changes, and the depletion of muscle mitochondria [17,18]. Although one study demonstrated that skeletal muscle change during neoadjuvant chemotherapy prior to RC is an independent predictor of ileus, infection, and other complications [19], conclusive data on the impact of sarcopenia in MIBC patients are not available due to limited evidence [20]. Conversely, the loss of skeletal muscle in metastatic urothelial bladder carcinoma has been demonstrated to be a significant predictor of 90-day mortality and postoperative complications [21].…”
Section: Introductionmentioning
confidence: 99%